Tailored Graphene Micropatterns by Wafer‐Scale Direct Transfer for Flexible Chemical Sensor Platform. Issue 2 (20th November 2020) - Kim, Yeonhoo; Kim, Taehoon; Lee, Jinwoo; Choi, Yong Seok; Moon, Joonhee; Park, Seo Yun; Lee, Tae Hyung; Park, Hoon Kee; Lee, Sol A; Kwon, Min Sang; Byun, Hyung‐Gi; Lee, Jong‐Heun; et al.
Abstract: 2D materials, such as graphene, exhibit great potential as functional materials for numerous novel applications due to their excellent properties. The grafting of conventional micropatterning techniques on new types of electronic devices is required to fully utilize the unique nature of graphene. However, the conventional lithography and polymer‐supported transfer methods often induce the contamination and damage of the graphene surface due to polymer residues and harsh wet‐transfer conditions. Herein, a novel strategy to obtain micropatterned graphene on polymer substrates using a direct curing process is demonstrated. Employing this method, entirely flexible, transparent, well‐defined self‐activated graphene sensor arrays, capable of gas discrimination without external heating, are fabricated on 4 in. wafer‐scale substrates. Finite element method simulations show the potential of this patterning technique to maximize the performance of the sensor devices when the active channels of the 2D material are suspended and nanoscaled. This study contributes considerably to the development of flexible functional electronic devices based on 2D materials. Abstract : A strategy to micropattern 2D materials on large‐scale flexible substrates using a direct polymer curing transfer method is demonstrated. Graphene microchannels on polymer substrates exhibit ultrahigh effective self‐heating under an applied bias voltage of less than 10 V. An entirely flexible and transparent chemical sensor array based on graphene micropatterns successfully discriminates gas species under the self‐activated state without external heating.